Practical suggestions in the writing of a research paper - Biswas Jyotirmay (Indian Journal of Ophthalmology, 1998)
Writing a scientific article requires proper planning and a methodical approach. This article provides practical tips to organize the materials before writing, and discusses how to approach the writing of different parts of an article; that is, introduction, materials and methods, results, and discussion. It also provides guidelines on authorship, citing references, selecting photographs, tables and legends, and finally on style, grammar and syntax.